Implementasi kebijakan model kerjasama pendidikan kesetaraan dalam meningkatkan pembangunan sumber daya manusia - Syamsuri Syamsuri; Sri Mujiarti Ulfah (Iapa Proceedings Conference, 2018)
Constitutional had been mandated in which every citizen had the right to get education and the state had the obligation to provide the facilities for each citizens who wished to enhance their education with the hope that there were not any children who would not go to school and dropped out. However, based on BPS data of Palangka Raya city, there were 0.36% or 936 people in Palangka Raya city dropped out. Because of that, Palangka Raya City Government through the Department of Education and Culture established a partnership with the PKBM Lutfillah Foundation to carry out an Equivalence Education program for people who dropped out. The purpose of this paper was to analyze the policy implementation for Enhancing Equivalence Education Cooperation Model in Palangka Raya city. This research method was carried out with a descriptive qualitative approach, data collection was carried out through observation, interviews and documents and also the analysis technique was with the interactive analysis model. The result of the reseach indicated that the cooperation model which was carried out for conducting socialization, implementing learning and conducting examinations. The government, the policy-maker, provided the budget and set the time for conducting the exam while the Luthfillah Foundation provided the facilities for the place of learning implementation and facilities for conducting examinations and socialization.